O enquadramento fotográfico enquanto possibilidade de região histórica - Silva, Fabiana Beltrami da (2017)
This study discusses urban photography in history. We propose to research the construction of an identity for the region of the city of Passo Fundo, in Rio Grande do Sul, from the photographic framing, realized through photographic studies and by amateur or professional photographers and their dialogues with the cultural context. The photographic framework was problematized from the perspective of its intrinsic potential to mark a region in history, from the photographic representations and the possibilities of selecting symbolic objects that are components of a given space. The research carried out a parallel between the practice of perpetrating photographic records of the city, in a broad and circumscribed way, analysing the city albums, the use of postcards, as well as the images published in local newspapers. The concepts of region, memory, photographic framing, urban photography and those related to the morphological constitution of the city, in its interfaces with the city of Passo Fundo, are approached. From the space of interest, the square Marechal Floriano and its surroundings - Independência Street, Bento Gonçalves Street and Morom Street, buildings, causeways and other uses and spatial senses, like the religious, cultural, political and railways - the history of the city and region is narrated together with 74 images, from the decade of 1910 until the contemporary. The main morphological objects of the city are delimited and observed through the reading of 27 photographic images, as well as the techniques utilized and the spaces they contemplated. The history of the photography of the city encompasses the uses of the images in Passo Fundo and aspects of what they represented, and still do, from the continuity of the current reproduction of the space, remaining in the collective memory of the region framed. Thus, in the end, the relation between photographic framing and region in the long historical and iconographic duration of the area in question is affirmed.